Results of the eighteenth winter waterbird census in Libya (IWC), January 2022 - Khaled Etayeb; Ashraf Galidana; Ali Berbash; Adulnasser Eisa; Ali Al-kordi; Elias Al-Helali; Mahmoud Abuhajar; Abdulati Alswyeb; Hussien Abdulqader; Nader Azabi; Nader Ghriba; Saleh Deryaq; et al. (Open Veterinary Journal, 2023)
Background: Libyan wetlands are diverse; the coastline of Libya in particular has different kinds of wetlands such as salt marshes, bays, lakes, lagoons and islands. These varieties in habitats provide good shelters and foraging sites for migratory birds during their journeys between Eurasia and Africa. Since the beginning of the Libyan winter census of waterbirds (Libya IWC) in 2005 which continued regularly until 2012, it had relatively the same performance in the number of covered sites. Since 2013, due to the security situation that Libya has experienced as a result of wars and conflict which negatively affected the quality of the IWC in Libya, the number of sites has dramatically decreased, reaching only 6 sites during the middle of the previous decade. Aim: The IWC 2022 aimed to counting the birds along the Libyan coast from January 10 to 29. Methods: The census activities were conducted from the dawn to dusk along the period of the study, by using high quality Telescopes, binoculars and digital cameras for the documentation. Point transects method was used to cover the sites. Results: The results of this year showed that a total of 64 sites were covered, 68 species of waterbirds were counted, with an abundance of 61,850 individuals. During the census period, a total of 52 non-waterbirds species found in Wetlands were recorded, and the number of individuals was 14,836 birds. A total of 18 threatened species were observed during this survey, 12 of them are mentioned in the IUCN Red-list, and 9 species are mentioned in the RAC/SPA annex II as threatened in the Mediterranean, where the species; Larus audouinii (Payraudeau, 1826), Larus genei (Breme, 1839) and Puffinus yelkouan (Acerbi, 1827) are mentioned in both of them. Conclusion: The lack of the number of Ornithologists and bird watchers is still one of the factors affecting the quality of the IWC in Libya, as well as lack of funding remains an important factor that plays a major role in the success of the waterbirds census. [Open Vet J 2023; 13(4.000): 407-418]